Morphology modulation of gas‐foamed, micrometric, hollow polystyrene particles. Issue 48 (19th August 2016) - Contaldi, Vincenzo; Imperato, Luigi; Orsi, Silvia; Di Maio, Ernesto; Netti, Paolo Antonio; Iannace, Salvatore
ABSTRACT: In this article, we reports the effects of the processing conditions on the morphological and hollow attributes of polystyrene micrometric hollow particles produced by the use of a recently developed technique based on the gas foaming of spherical, dense particles. By modulating the foaming temperature and saturation pressure, we produced hollow particles with different attributes in terms of hollow dimensions, eccentricity, and open–close features. The results from these small systems were compared, and we found agreement with what is typically observed in bulk polymeric foaming, for example, an increase in the foaming efficiency with saturation pressure and the nonmonotonic effect of temperature. Furthermore, we observed an increase in the hollow number when using nucleating agents with respect to the neat polymer and when using nitrogen with respect to carbon dioxide as the blowing agent. The effects of particle manipulation before foaming to achieve hollow elongated or distorted particles are also reported. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44236. Abstract :